Online Research Portal - Lumauag, Ramil G. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
A Web Portal is a website or service that offers a broad array of resources and online services, such as search engines, directories, news, e-mail, and online information. Portals have evolved to provide a customized gateway to Web information. This study aimed to develop an Online Research Portal. Specifically, it aimed to create an online repository of researches and articles, publish researches and articles online, manage web content, distribute content depending on the user privileges and access level, create a venue for collaboration with other research institutions, create linkages with other research institutions, access information while off-campus, and disseminate latest update on research. An Evolutionary Prototype Model was used to develop the system and a test case was used to test the functionality. The respondents of the study were the randomly selected 25 Faculty of ISAT U Miagao Campus as well as 5 IT Experts coming from different sectors, and the system was evaluated by the IT Experts and Faculty using ISO 9126 software quality characteristics such as functionality, reliability, usability, efficiency, maintainability, and portability. Mean and standard deviation were used as statistical tool for this study. The experts’ evaluation of the system based on ISO 9126 criteria is effective and the faculty evaluation is very effective. The overall result of the evaluation is very effective, and the system meets the criteria for software quality characteristics; therefore, it is recommended to be implemented.